Driving change: the role of "emotional connectedness" – a case study. Issue 5 (11th July 2016) - Lacoste, Sylvie M.; Dekker, Janet
Abstract : Purpose: The purpose of this paper is to understand which change process the supplying organization should define for its customer-facing organization in order to successfully increase customer orientation and to be on the short list of their customers' key suppliers. Design/methodology/approach: Action research was used to carry out this research. Researchers were involved in the change management process of a medium-sized company that wanted to re-design their customer selection and interaction processes: one researcher was a top manager of the participating company, whereas the other researcher worked alongside the organization in a collaborative effort to introduce and roll out sales force training seminars. Findings: Researchers' main finding shows how the company's top-management willingness to apply a "soft" approach to change leverages a concept called "emotional connectedness". Originality/value: The authors bridge a gap between the literature on change management and the "emotional connectedness" concept related to social psychology. The authors add to existing theories on change management a new perspective based on interpersonal relationships.